#### Answer

Does not make sense.
Take for example the equation:
$x^2 - bx = c$
Adding a negative constant will only affect the constant term $c$, and will not get you closer to completing the square. It will, in fact, give you an equation where you still need to isolate the binomial term.
$x^2 - bx -c = c -c$
$x^2 - bx -c = 0$
Instead, what you need to do is to get the square of half the value of the coefficient of the $x$-term, and add this on both sides to complete the square.
$x^2 - bx + (\frac{-b}{2})^2= c +(\frac{-b}{2})^2$